Investigations towards lower cooling load in a typical residential building in Kurdistan (Iraq). (November 2020) - Mustafa, Mahmud; Ali, Samira; Snape, J. Richard; Vand, Behrang
Abstract: Energy consumption in cooling the buildings and occupant's thermal comfort is significant, and any techniques to reduce this can bring great benefits, both locally in terms of reducing the need for expensive infrastructure and globally in terms of reduced carbon emissions. This study focuses on Northern Iraq, Kurdistan. This area suffers from a shortage of electricity production, alongside a high and growing demand due to the rapid expansion in the residential building sector over the last few decades through investment projects. The cooling energy performance of a typical house in Kurdistan was simulated, using DesignBuilder and EnergyPlus software. The study identified the most effective parameters of the building fabrications to be applied for enhancing the energy performance of residential buildings such as insulation, suspended ceiling, window glazing, overhang, and block type. The study found the parameters with the most impact on energy consumption to be suspended ceiling and insulation that could save a high rate of energy consumption. The impact of the clear double glazing and overhang of the windows are generally low, due to the low window/wall ratio and the availability of the internal curtain in the building. Finally, the optimum parameter values are identified and used in energy demand simulations, it showed that by using the optimum parameters of the building fabrications, 28.35% of the annual energy used could be saved from cooling in the house module.